Respuesta :
Answer:
[tex]x = \frac{1}{2} [/tex]
[tex]y = 3[/tex]
Step-by-step explanation:
Multiply the bottom equation by -2.
[tex] - 2( - 2x - y = - 2) = - 4x + 2y = 4[/tex]
Add the new equation to top equation.
[tex]5y = 15[/tex]
[tex]y = 3[/tex]
Know plug 3 in one of the equations to find x.
[tex]4x + 3(3) = 11[/tex]
[tex]4x = 2[/tex]
[tex]x = \frac{1}{2} [/tex]
Answer:
( [tex]\frac{1}{2}[/tex], 3 )
Step-by-step explanation:
Given the 2 equations
4x + 3y = 11 → (1)
2x - y = - 2 → (2)
Multiplying (2) by 3 and adding to (1) will eliminate the y- term
6x - 3y = - 6 → (3)
Add (1) and (3) term by term to eliminate y
10x + 0 = 5
10x = 5 ( divide both sides by 10 )
x = [tex]\frac{1}{2}[/tex]
Substitute x = [tex]\frac{1}{2}[/tex] into either of the 2 equations and solve for y
Substituting into (1)
4 ([tex]\frac{1}{2}[/tex] ) + 3y = 11
2 + 3y = 11 ( subtract 2 from both sides )
3y = 9 ( divide both sides by 3 )
y = 3
solution is ( [tex]\frac{1}{2}[/tex], 3 )